2007
DOI: 10.1007/s00586-007-0373-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the lumbar spine in trunk rotation: in vivo three-dimensional analysis using magnetic resonance imaging

Abstract: In vivo three-dimensional (3D) kinematics of the lumbar spine has not been well evaluated by the conventional methods because of their methodological limitations, while 3D intervertebral motions have been quantitatively determined by cadaver studies. We thus developed a novel 3D analyzing system for the relative motions of individual vertebrae using 3D magnetic resonance imaging (MRI) and analyzed in vivo 3D intervertebral motions of the lumbar spine during trunk rotation. Ten healthy volunteers underwent 3D M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 16 publications
2
58
0
Order By: Relevance
“…For example, coupled motion was not included in our model despite data showing that lateral bending and axial rotation are usually accompanied by motion in the other two degrees-of-freedom (White and Panjabi 1978a;Pearcy and Tibrewal 1984;Ochia et al 2006;Fujii et al 2007;Kozanek et al 2009;Li et al 2009). This was because the ensuing change in the results was not significant enough to justify the increase in computational cost as a result of the increase in the model's complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, coupled motion was not included in our model despite data showing that lateral bending and axial rotation are usually accompanied by motion in the other two degrees-of-freedom (White and Panjabi 1978a;Pearcy and Tibrewal 1984;Ochia et al 2006;Fujii et al 2007;Kozanek et al 2009;Li et al 2009). This was because the ensuing change in the results was not significant enough to justify the increase in computational cost as a result of the increase in the model's complexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data were normalized to 25 • in accordance with the ROM of the lumbar spine in lateral bending as mentioned in the study by Troke et al (2001). Axial rotation motion of the model was based on data presented in Fujii et al (2007). 1 Table 3 summarizes the slope values used for each of the five lumbar levels.…”
Section: Joint Kinematicsmentioning
confidence: 99%
“…Ochia et al [21] used 3D CT scan to investigate the passive lumbar axial rotation in a supine body position by ±50°. Fujii et al [19] performed in vivo non-weight bearing supine MRI scan of human lumbar spine at different passive axial rotation of the upper body by 15°increments to the maximum trunk rotation. These studies showed, on average, \2°in axial rotation at each vertebral level, and a similar trend in the coupled bending motion in the L2-L4 The percentages of segmental ROM with respect to total ROM are shown in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the in vivo studies have used skin markers or plain radiographs to measure the vertebral motion during various dynamic motion or static postures [16][17][18]. Three-dimensional CT and MRI imaging techniques have also been used to determine the vertebral motion during passive axial rotation of the lumbar spine [19][20][21]. Recently, a 3D fluoroscopic imaging technique was applied to investigate the 6DOF static range of motion of lumbar vertebrae at various weight bearing body postures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A 45°axial trunk rotation has been shown to result in a 1.7°and 1.6°axial rotation at L4-5 and L5-S1 respectively. 7 In our study we applied a rotation of 3°over these two levels, which would therefore correspond to a 41°trunk rotation. Clearly this level of trunk rotation is common in a wide range of sporting and daily activities.…”
Section: Discussionmentioning
confidence: 99%